1985
DOI: 10.1161/01.cir.71.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Sustained improvement of pulmonary hemodynamics in patients at rest and during exercise after thrombolytic treatment of massive pulmonary embolism.

Abstract: This study assessed the long-term effects of thrombolytic treatment in patients with acute massive pulmonary embolism (PE). Seven patients with PE that followed deep-vein thrombosis underwent pulmonary angiography and pressure measurements before and 6 ± 3 days (mean ± SD) and 15 ± 4 months after treatment with intrapulmonary infusions of urokinase (average dose 1724 U/ kg.hr) and heparin (average dose 17 U/kg.hr). Treatment was guided by daily measurements of pulmonary arterial (PA) pressure and was continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…15 In a long-term follow-up study carried out 4 years after the initial embolic episode, DeSoyza and Murphy 16 reported high resting PA pressures with an abnormal elevation on exercise in 9 (69%) of 13 patients. In contrast with the persistent post-embolic pul-Vascular Medicine 2000; 5: 91-95 monary hypertension in the above studies, Schwarz et al 17 reported sustained improvement of pulmonary hemodynamics both at rest and during exercise in six (85%) of the seven patients who were treated with urokinase for massive PE and studied 15 months later.…”
Section: Discussionmentioning
confidence: 91%
“…15 In a long-term follow-up study carried out 4 years after the initial embolic episode, DeSoyza and Murphy 16 reported high resting PA pressures with an abnormal elevation on exercise in 9 (69%) of 13 patients. In contrast with the persistent post-embolic pul-Vascular Medicine 2000; 5: 91-95 monary hypertension in the above studies, Schwarz et al 17 reported sustained improvement of pulmonary hemodynamics both at rest and during exercise in six (85%) of the seven patients who were treated with urokinase for massive PE and studied 15 months later.…”
Section: Discussionmentioning
confidence: 91%
“…There is some evidence that thrombolysis results in favorable quality‐of‐life outcomes, when compared with anticoagulation alone . However, recent studies have failed to show a definite effect of thrombolysis on right ventricular function and functional outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines recommend systemic IV thrombolysis for patients with high-risk PE and no contraindications, as thrombolysis has been associated with improvement in hemodynamics and right ventricular function. 3,15,[28][29][30][31] The role of systemic thrombolysis in intermediate-risk PE, however, remains controversial. Two recent randomized, placebo-controlled clinical trials, the Tenecteplase Or Placebo in the Care Of Acute Thromboembolism (TOPCOAT) and the Pulmonary Embolism Thrombolysis (PEITHO) studies, evaluated the role of systemic thrombolysis in intermediate-risk PE.…”
Section: Systemic Intravenous Thrombolysismentioning
confidence: 99%